2019
DOI: 10.1088/1361-6579/ab031c
|View full text |Cite
|
Sign up to set email alerts
|

Predicting forced vital capacity (FVC) using support vector regression (SVR)

Abstract: Objective: Spirometry, as the gold standard approach in the diagnosis of chronic obstructive pulmonary disease (COPD), has strict end of test (EOT) criteria (e.g. complete exhalation), which cannot be met by patients with compromised health states. Thus, significant parameters measured by spirometry, such as forced vital capacity (FVC), have limited accuracies. To address this issue, the present study aimed to develop models based on support vector regression (SVR) to predict values of FVC under the condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…When patients with AECOPD cannot complete the pulmonary function test, we can preliminarily judge whether a patient has a severe episode and the predicted values of FEV 1 and FVC can be easily accessed. Compared with the study by Wang et al (2019) in which acceptable FVC values can be obtained by reducing the degrees of the EOT criteria to an extent, this approach achieved comparable accuracy on the basis that patients no longer need to exhale at all, which can be used to predict pulmonary function indexes during AECOPD. Some demographic parameters, including height, may be affected by other factors including osteoporosis; and this will confound the interpretation of comparisons made to a predicted normal value for pulmonary function that has been determined based upon a patient's height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When patients with AECOPD cannot complete the pulmonary function test, we can preliminarily judge whether a patient has a severe episode and the predicted values of FEV 1 and FVC can be easily accessed. Compared with the study by Wang et al (2019) in which acceptable FVC values can be obtained by reducing the degrees of the EOT criteria to an extent, this approach achieved comparable accuracy on the basis that patients no longer need to exhale at all, which can be used to predict pulmonary function indexes during AECOPD. Some demographic parameters, including height, may be affected by other factors including osteoporosis; and this will confound the interpretation of comparisons made to a predicted normal value for pulmonary function that has been determined based upon a patient's height.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the model can be used to predict FEV 1 values of normal and abnormal subjects. Wang et al (2019) proposed prediction models based on age, gender, FEV 1 and peak expiratory flow (PEF) to estimate forced vital capacity (FVC) when the end-of-test (EOT) criteria in conventional spirometry was not met. The results of the model operation showed that the measured FVC value was positively correlated with the predicted one, and the Pearson correlation coefficient of the best model was 0.98.…”
Section: Introductionmentioning
confidence: 99%
“…The best result was shown by the linear regression model; the coefficient of determination R was equal to 0.991, the average absolute error MAE was equal to 0.014, and the root of the root mean square error RMSE was equal to 0.017. The authors of the scientific work [9] developed a model based on the support vector regression (SVR) method to predict the values of forced vital capacity.…”
Section: Introductionmentioning
confidence: 99%